Characterization of anemia induced by avian osteopetrosis virus. - Paterson, R W (1978)
Chickens infected intravenously at 8 days after hatching with an avian osteopetrosis virus developed a severe, progressive anemia in the absence of osteopetrosis. The anemia was characterized as a pancytopenia, in which erythrocytes, granulocytes, and thrombocytes decreased concomitantly. Serum bilirubin levels were normal, whereas erythrocytes from infected chickens demonstrated a slightly elevated osmotic fragility. A negative Coombs test indicated that there was no evidence for erythrocyte-bound antibody. Erythrocytes from infected animals had slightly decreased 51Cr-labeled erythrocyte survival time when compared with normal. Examination of marrow histological preparations, together with ferrokinetic studies with 59Fe, indicated that marrow failure occurred during the acute phase of the anemia. Circulating virus was present during the development and acute phases of the anemia, but disappeared during the recovery phase of the disease. Neutralizing antibody appeared after the disappearance of circulating virus. It is concluded that virus infection induced both marrow failure (aplastic crisis) and decreased erythrocyte survival.